CAUSES AND CONSEQUENCES OF THE WAR ON MARIJUANA IN INDONESIA - Pangaribuan, Aristo Marisi Adiputra; Manthovani, Kelly (UI Scholars Hub, 2019)
This article argues that the current narcotics law regime is a factor to blame for the cause of prison overcrowding and unnecessary deprivation of liberty and dignity for its violator with the help of criminal justice tools. Multi-layer category of drug users introduced by the current narcotics law is leaving too much discretion for the law enforcement agency to criminalize marijuana user. Data shows that in Jakarta and Surabaya court alone, all marijuana users are charged with multiple articles and leaving no room for them to escape from a draconian sentence. This paper questions the repressive enforcement used by the Indonesian apparatus specifically on marijuana because it leads to other issues bigger than the personal use of marijuana itself. In the end, this article is proposing the change of legislation in marijuana law while at the same time taking the nature of political conservatism in Indonesia into account.